Learning optimal strategies in a duel game - Angelos Gkekas; Athina Apostolidou; Artemis Vernadou; Athanasios Kehagias (Games, 2025)
We study a duel game in which each player has incomplete knowledge of the game parameters. We present a simple, heuristically motivated and easily implemented algorithm by which, in the course of repeated plays, each player estimates the missing parameters and consequently learns his optimal strategy.
Keywords: 330; duel game; tree game; backward induction; incomplete information; learning